Preparation of calcium peroxide from liquid waste of the Kungrad soda plant and use in thepulp industry - Abdurakhim Nabiyev; Firuza Abdiyeva; Yunusova Guzal (Genius Journals, 2025)
Soda ash is the main product of the chemical industry, which is used in glass production, the metallurgical, the pulp and paper industry and other. Currently,industry uses the Solvay method to produce soda ash
Keywords: Solvay method; distiller liquid